Have prices of internationally traded steam coal been marginal cost based? - Johannes Trueby; Moritz Paulus (Institute of Energy Economics at the University of Cologne (EWI), 2010)
During 2007 and 2008 steam coal prices soared to unprecedented levels. Since then much has been speculated about the drivers of these price peaks. This paper is concerned with the costs of steam coal allocation in the seaborne market and their influence on the price equilibrium. It presents an optimisation model that differentiates between mining technologies and therefore allows to analyse the effects of input price escalation on marginal costs in detail. Since 2005 input prices of commodities used in coal mining and bulk carrier freight rates increased significantly, causing marginal costs to rise. However, this affected suppliers along the global supply curve differently. We find that low-cost intramarginal suppliers experienced higher cost increases than marginal suppliers due to the different production technologies applied. Based on our results we conclude that prices of internationally traded steam coal are generally marginal cost based. However, the all time price spike of 2008 was not caused by cost escalation. We suppose that short-run capacity scarcity was responsible for the soaring prices in this year. Hence, marginal costs are a major determinant of the price equilibrium in the seaborne steam coal market given that capacity is not scarce.
Keywords: C61; L11; L71; Q31; 330; Steam coal; marginal costs; mining technologies; cost escalation; price peak; Kohle; Preis; Außenhandelspreis; Grenzkosten; Kohlenbergbau; Technologie; Welt